Census of Federal Law Enforcement Officers (CFLEO), (United States), Fiscal Year 2020 ([Verlag nicht ermittelbar], 2023)
The 2020 Census of Federal Law Enforcement Officers (CFLEO) collects information from federal law enforcement agencies that are authorized to make arrests and/or carry firearms. Data describe the number of officers employed by the agencies, the demographic characteristics of the officers, the functions of the officers, as well as hiring policies, screening techniques, equipment, and use of force techniques employed by these agencies.